Pengaruh Dana Desa dan Alokasi Dana Desa Terhadap Kemiskinan Antar Kabupaten di Provinsi Sulawesi Tenggara - Ernawati; Halulanga, Ferawati; Bachmid, Gamsir (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the effect of village funds and village fund allocations on poverty between regencies in Southeast Sulawesi Province. This study is a quantitative study using secondary data. The secondary data used in this study is panel data. Panel data is obtained from a combination of time series data and data from several objects at one time (cross section). The panel data in this study are Village Fund data, Village Fund Allocation and Poverty, using 15 regencies in Southeast Sulawesi Province and in the last 5 years from 2019 - 2023. The results of the study show that Village Funds and Village Fund Allocations have a negative and significant effect on the Poverty variable between regencies in Southeast Sulawesi Province. In this case, the Government is expected to continue the Village Fund and Village Fund Allocation programs to eradicate poverty and strive so that people do not experience poverty again.